PINK1-PARK2-mediated mitophagy in COPD and IPF pathogeneses - Kazuya Tsubouchi; Jun Araya; Kazuyoshi Kuwano (BMC, 2018)
Abstract Mitochondria regulate not only cell functions through energy generation but also aging-associated cell phenotypes. Impaired mitochondrial structural and functional integrity accompanied by excessive mitochondrial reactive oxygen species (mtROS) production is associated with enhanced programmed cell death (PCD) and cellular senescence. Dysregulation of mechanisms for mitochondrial integrity, including mitophagy, induces accumulation of mitochondrial damage. Mitophagy is a highly conserved mechanism of selectively delivering damaged mitochondria for lysosomal degradation and is mainly governed by phosphatase and tensin homolog (PTEN)-induced putative protein kinase 1 (PINK1) and PARK2. Accumulating evidence suggests that PINK1-PARK2-mediated mitophagy has an important role in the pathogenesis of aging-associated pulmonary disorders, represented by chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrosis (IPF). COPD characterized by progressive airflow limitation is mainly caused by cigarette smoke (CS) exposure, and accumulation of damaged mitochondria in bronchial epithelial cells (BEC) has been demonstrated. Intriguingly, both enhanced and impaired mitophagy have been implicated in COPD pathogenesis. Enhanced mitophagy induced by increased PINK1 expression has been associated with programmed necrosis, necroptosis. On the other hand, reduced PARK2 levels were linked to insufficient mitophagy, resulting in accelerated cellular senescence in BEC. Although dominant involvement of PCD and cellular senescence remains unclear, PINK1-PARK2-mediated mitophagy regulates mitochondrial ROS and cell fate during COPD pathogenesis. Involvement of insufficient mitophagy has been proposed in lung fibrosis development during IPF pathogenesis. Accumulation of dysmorphic mitochondria and increased ROS production linked to decrease in PINK1 expression were demonstrated in type II alveolar epithelial cells (AECIIs) in IPF lungs, which can be associated with enhanced apoptosis and cellular senescence. Furthermore, reduced PARK2 expression levels have been shown in myofibroblasts in IPF lungs. Insufficient mitophagy caused by PARK2 deficiency induced mtROS production with concomitantly activated platelet-derived growth factor receptor (PDGFR)/mammalian target of rapamycin (mTOR) signaling, resulting in increased myofibroblast differentiation and proliferation. Inappropriate PINK1-PARK2-mediated mitophagy appears to be mainly responsible for regulating cell fate, including PCD, cellular senescence, and myofibroblast differentiation during COPD and IPF pathogeneses. Modalities to achieve specific and appropriate levels of PINK1-PARK2-mediated mitophagy activation may be a promising therapeutic option to regulate the aging-associated pathology, COPD, and IPF.